Uneven Distribution Possibilities of Creative Capital Development in Rural Aareas (Case Study of the Podkarpackie Communes, Poland) - Szara, Katarzyna (Eastern European Countryside, 2024)
This paper presents the results of the research, which is an attempt to modify the assumptions of R. Florida’s theory regarding the creative class. The measurement is based on indices that are the basis for the measurement of three categories: talent, technology, tolerance is not always possible due to the lack of data. The purpose of the study was to identify factors determining activation of creative capital in the areas of communes (local level). The objective results from the need to determine whether or not such conditions are present at the local level. Using the available literature, a questionnaire was prepared. Its results obtained from a survey among the Podkarpackie residents, were presented in the paper. It was found, as in the case of the results of the work of other authors, that in municipal communes there were better conditions for the development of creative capital.